Pre-challenge and post-challenge haemato-immunological changes in Oreochromis niloticus (Linnaeus , 1758) fed argan oil against Lactococcus garvieae - Baba, Esin; Acar, Ümit; Yılmaz, Sevdan; Öntaş, Canan; Kesbiç, Osman Sabri (Wiley, 2017)
The present study investigated the effects of argan oil, obtained from Argania spinosa, on pre- and post-challenge immuno-haematological and biochemical responses of Nile tilapia, Oreochromis niloticus. For this purpose, the fish were fed diets containing 0, 0.5%, 1% or 2% argan oil for 45days. Following 45days of feeding, fish were challenged with Lactococcus garvieae and mortality was recorded for 15days. During the pre-challenge period, significantly higher respiratory burst activity, total white blood cell (WBC), serum lysozyme activity and myeloperoxidase activity were determined in the argan oil-fed groups. The serum glucose and cholesterol levels decreased whilst total protein and albumin did not change in the groups fed with argan oil-supplemented diets. After challenge with Lactococcus garvieae, the percentage survival (%) was found to be the highest in the 1% and 2% argan oil-supplemented feeding groups. Also, there was a significant increase in weight gain, specific growth rate and feed conversion ratio in those fish fed argan oil. The results of this study indicated that after the supplementation of fish diets with argan oil, especially at 1% and 2% concentrations, the immunological, haematological and biochemical values remained similar in both the pre- and post-challenge periods and the immune response against L. garvieae in Nile tilapia was modulated.
Keywords: 14. Life underwater; 3. Good health